Determinación de la cantidad de biomasa acumulado, en cada ciclo evolutivo del maíz (zea mays L.), en dos condiciones climáticas de Lamas - Ruíz Soria, Nino Fernando (2014)
The present rescarch project is developed in the district and provincc of Lamas in the Region San Martín. Field phase was carricd out in two periods, which have different climatic conditions. The first installation was from January to April 2014, and the second from June to September 2014. The specific objectives were to: assess the biomass, the captured C02, among other quantitative parameters, each evolutionary cycle of corn, planted in two consecutive seasons, and to relate the climatic conditions with the biomass accumulated at each evolutionary cycle of corn. The statemcnt of the problem cstablishcd was how much is thc increase of biomass hetwccn each evolut.ionary cycle "corn" (Zea mays Linn.), in two climatic conditions of Lamas?. Between the variables and independent variables, the evolutionary cycle of the corn, the dcpendcnt variable, the amount of accumulated biomass. Thc hypothesis to dcmonstrate was, if we evaluate the biomass at each cvolutionary cycle of corn, in two climatic conditions of Lamas, then thcrc is highly significant among them. The results were: To assess biomass of "corn" (Zea mays Linn), during the first season (January to April - 20 14) was 1142.45 grams per plant dry matter, and 250.32 g of C. This indicates that the 21.91% of the weight of the dry matter accumulated per plant is carbon, captured at 90 days of age of the plant. The biomass of corn, in the second sowing season (June to September - 2014), prescnted 880.33 grams of dry mattcr 1 plant and 212.912 grams of carbon pcr plant. lt was thcn dctcrmined that thc 24.19% of thc weight of the dry matter is carbon on each floor. When thc rclationship between the climatic conditions with the biomass accumulated at cach cvolutionary cycle of corn, we find the following data: In the first period: the re.lationship between the dry hiomass and the T o mcdium prescnted a Iow ratio, indicatcd by the cocfficicnt of correlation r = 0.07, according to road, l995.thc cocfficicnt r2 was 0.005. The value of b = 3.9, thc rcgrcssion coefficient. In the sccond planting time evaluatecl during the dry months in Lamas (June - Scptembcr), the rclationship hetwecn thc dry hiomass and the T " average, are cxpressed with valucs: r = 0.3, r2 = 0.09, and b = 32.1. Which indicatc that you prcsentcd a positive relationship. The results hc.lped to prove thc hypothesis raised about the differencc m biomass betwcen other parametcrs, in two climatic conditions of Lamas.